Prevalence and severity of carious lesions in children from 5 to 9 years old of the Remigio Crespo Toral Basic Education School, Cayambe, Ecuador* - Martínez-Freire, Alexandra Cumanda; Saquicela-Pulla, María Gabriela; Armas-Vega, Ana del Carmen (Revista Facultad de Odontología Universidad de Antioquia, 2025)
Introduction: Dental caries is a chronic non-communicable disease and a global public health problem that affects human well-being and development. Its multifactorial origin involves biological, psychological and social factors. In Ecuador, data on its prevalence are limited. The aim of the present study was to determine the prevalence and severity of carious lesions in children aged 5 to 9 years from the “Remigio Crespo Toral” elementary school in Cayambe, Ecuador, using the International Caries Detection and Assessment System (ICDAS II). Methods: A cross-sectional study was carried out in 229 children, with prior authorization from CEISH - UNIANDES, Ecuador, whose parents authorized their participation by means of informed consent. Intraoral clinical examinations were carried out using portable equipment and following biosafety standards. Data were collected using alphanumeric cards, recording age, sex, presence and severity of carious lesions according to ICDAS II codes. Statistical analysis was performed with R software (v4.4.4.1) using median tests and 95 % confidence intervals. Results: There was an increase in carious lesions in the primary teeth with age. ICDAS code 2 was the most prevalent. Temporal molars and first permanent molars were the most affected teeth. Conclusion: The prevalence of dental caries increases with age in the primary dentition, with ICDAS code 2 being the most prevalent. In the permanent dentition, the first molars were the most affected. No significant differences were observed according to sex. * This manuscript is derived from dissertations or theses, which are in the process of being entered into the repository of the Universidad Hemisferios, Quito, Ecuador.